2001
DOI: 10.1034/j.1600-0625.2001.010003175.x
|View full text |Cite
|
Sign up to set email alerts
|

Metalloelastase (MMP‐12) and 92‐kDa gelatinase (MMP‐9) as well as their inhibitors, TIMP‐1 and ‐3, are expressed in psoriatic lesions

Abstract: In skin biology, matrix metalloproteinases (MMPs) have been implicated in inflammatory matrix remodeling, neovascularization, wound healing and malignant transformation. Psoriasis is histologically characterized by keratinocyte hyperproliferation, infiltration of inflammatory cells, neoangiogenesis and production of cytokines, such as TNF-alpha, IL-1beta, TGF-alpha, and IFN-gamma, also capable of regulating MMP transcription. To investigate the role of stromelysins-1 and -2, matrilysin, metalloelastase, collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 55 publications
0
40
0
1
Order By: Relevance
“…Since MMP-12 is not only involved in lung tissue remodeling-associated diseases [35,37,41,46,50,[81][82][83][84][85][86][87][88][89], substantial efforts have been made to develop MMP-12 synthetic inhibitors. However, inhibiting a specific MMP is a difficult goal because of the high conservation between many MMPs in terms of overall 3D-structure, topology of the catalytic domain and requirement of specific amino-acid residues in the active site [90,91].…”
Section: Most Efficient Mmp-12 Chemical Inhibitorsmentioning
confidence: 99%
“…Since MMP-12 is not only involved in lung tissue remodeling-associated diseases [35,37,41,46,50,[81][82][83][84][85][86][87][88][89], substantial efforts have been made to develop MMP-12 synthetic inhibitors. However, inhibiting a specific MMP is a difficult goal because of the high conservation between many MMPs in terms of overall 3D-structure, topology of the catalytic domain and requirement of specific amino-acid residues in the active site [90,91].…”
Section: Most Efficient Mmp-12 Chemical Inhibitorsmentioning
confidence: 99%
“…25 The MMP9 protein is induced by TNF-α and is in psoriatic lesions produced by macrophages and neutrophils. 26 In a study of psoriatic arthritis, infliximab treatment led to a reduction in the MMP9 and sE-selectin serum levels, together with a reduction in the spontaneous release of MMP9 and sE-selectin from lesional skin. 27 Therapy with TNF-α inhibitor also leads to a reduction in MMP9 in peripheral blood mononuclear cells, plasma and in psoriatic lesions.…”
Section: T Cells and Langerhans Cells Of The Inflammatory Infiltratementioning
confidence: 99%
“…22 A previous report showed that laminin c1 from laminin 511 can be degraded by MMP-9, 23 which is highly expressed in the psoriatic skin lesions. 22 Increase of laminin c1 fragments that are processed by MMP-9 in psoriatic lesions may initiate the production of anti-laminin c1 autoantibody, which binds to the essential site for molecular interaction in the basement membrane zone of the skin. Several lines have suggested that expression of integrins is modified in the basement membrane zone of psoriatic skin.…”
Section: Laminin and Psoriasismentioning
confidence: 99%